Characterization of school of dentistry prerequisite courses and recommendations for admission. Issue 3 (22nd October 2020) - Wolcott, Michael D.; Reside, Jonathan M.; Bobbitt, Laura J.; Quinonez, Rocio B.
Abstract: Purpose: There is minimal research characterizing admission prerequisites courses across schools of dentistry. The purpose of this study was to typify didactic and laboratory course requirements and compare requirements based on institution demographics. Methods: In July 2019, the researchers evaluated websites from 76 North American dental schools to collect information on required and recommended courses, credit hour requirements, and institution demographics. Sub‐group analyses evaluated differences in course and credit hour differences based on institution funding, degree program, location, and Carnegie Classification. Results: The most common required courses were general chemistry (97.4%), physics (93.4%), organic chemistry (92.1%), general biology (90.8%), communication (86.8%), and biochemistry (80.3%). The most common required laboratory courses were general chemistry (63.2%), organic chemistry (59.2%), general biology (55.3%), and physics (51.3%). Several institutions included unique course recommendations such as histology (40.7%), psychology (30.3%), art (18.4%), business (18.4%), sociology (15.8%), and embryology (14.5%). There were few differences based on institution classifications; however, differences were observed most often between institutions within and outside the United States. The study also identified 65.8% (n = 50) of schools have letter of recommendation requirements and 46.1% (n = 35) of schools require or recommend shadowing experiences with programs requesting a median of 60 hours (range 20‐300 hours). Conclusions: The study offers a contemporary characterization of prerequisite requirements and recommendations. In addition, the study raises critical questions about whether these standards reflect expectations for entering learners, if these requirements truly relate to learner success, and if these requirements prepare learners to be future‐ready graduates.